Bioinspired Manganese and Iron Complexes with Tetradentate N Ligands for the Asymmetric Epoxidation of Olefins. Issue 8 (21st May 2013) - Wang, Xiaoe; Miao, Chengxia; Wang, Shoufeng; Xia, Chungu; Sun, Wei
Abstract The manganese and iron complexes with the tetradentate N ligand (1R, 2R)‐N, N'‐dimethyl‐N, N'‐bis(1‐methyl‐2‐benzimidazolylmethyl)cyclohexane‐1, 2‐diamine have been synthesized and characterized. The crystal structure of the manganese complex demonstrates a cis‐α configuration. Both the manganese and iron complexes are active catalysts for the asymmetric epoxidation of olefins with H2O2 as an oxidant and acetic acid as an additive. Up to 96 % ee was observed for the epoxidation of α, β‐unsaturated ketones at −20 °C.